Correlation of Selenium and other antioxidants in diabetic patients with and without complications - Kumar, Robby (Free Radicals and Antioxidants)
Background: Diabetes mellitus causes free radicals generation which is one of the major causes for the complications in diabetes mellitus. Objective: To investigate whether selenium level differs between Type 2 diabetic subjects with and without complications and correlate with antioxidant status. Methodology: Subjects were divided into group-I-Diabetics without any complications and Group-II-Diabetics with complications. Serum Glucose, Lipid Profile, Selenium was estimated along with reduced Glutathione, Superoxide dismutase and Thiobarbituric acid reacting substances in both the groups and they were compared with healthy controls. Results: Serum selenium and other markers of oxidative stress were found to be statically decreased in both the groups when compared with control. Conclusion: there is a significant reduction in selenium in serum as the disease progresses; hence reduced selenium indicates metabolic response towards the oxidative stress in patients with diabetes. Thus, selenium can be used in diabetics to prevent late complications.
Keywords: Antioxidants; Diabetes mellitus; Selenium; Lipid Peroxidation